1994
DOI: 10.1002/tera.1420500208
|View full text |Cite
|
Sign up to set email alerts
|

Ebstein's malformation of the tricuspid valve: Genetic and environmental factors

Abstract: Ebstein's anomaly is a specific structural deformity of the tricuspid valve, and its rarity has hampered etiologic evaluation. Cases of Ebstein's anomaly registered in the Baltimore Washington Infant Study (BWIS), a regional case-control study of cardiovascular malformations (CVM) in infancy, are reviewed. Between 1981 and 1989 a total of 4,390 CVM cases, including 47 Ebstein cases, and 3,572 controls were registered. The prevalence of Ebstein's anomaly was 5.2 per 100,000 livebirths. Additional cardiac anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
103
5
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 35 publications
(1 reference statement)
11
103
5
2
Order By: Relevance
“…Case-control studies suggest genetic, reproductive, and environmental risk factors (eg, the anomaly is more common in twins, in those with a family history of congenital heart disease, and in those with maternal exposure to benzodiazepines). 4 Maternal lithium therapy can rarely lead to Ebstein's anomaly in the offspring. 20 Most cases are sporadic; familial Ebstein's anomaly is rare.…”
Section: Prevalence and Genetic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case-control studies suggest genetic, reproductive, and environmental risk factors (eg, the anomaly is more common in twins, in those with a family history of congenital heart disease, and in those with maternal exposure to benzodiazepines). 4 Maternal lithium therapy can rarely lead to Ebstein's anomaly in the offspring. 20 Most cases are sporadic; familial Ebstein's anomaly is rare.…”
Section: Prevalence and Genetic Factorsmentioning
confidence: 99%
“…[2][3][4][5][6] This anomaly was described by Wilhelm Ebstein in 1866 in a report titled, "Concerning a very rare case of insufficiency of the tricuspid valve caused by a congenital malformation." 7,8 The patient was a 19-year-old cyanotic man with dyspnea, palpitations, jugular venous distension, and cardiomegaly.…”
mentioning
confidence: 99%
“…Environmental factors implicated in aetiology include maternal ingestion of lithium or benzodiazepine and maternal history of miscarriage. 2 Increased incidence is observed in Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Other than the findings among lithium-exposed infants in the International Register, most of the information on the safety of lithium during pregnancy that has accumulated in the past 40 years is based on case reports [10][11][12][13][14] and small studies (Table S1 in the Supplementary Appendix, available with the full text of this article at NEJM.org). Several small casecontrol studies failed to show an association between lithium and Ebstein's anomaly, [15][16][17][18][19] overall cardiac defects, 20 or any congenital malformations. 21 In two uncontrolled cohort studies of lithium-exposed pregnancies, no cardiac malformations were detected in the 82 newborns examined 22,23 ; another uncontrolled study showed four mild cardiac defects in 79 exposed infants.…”
mentioning
confidence: 99%